(untitled) (Revista INTEREDU11, 2023)
Migratory movements are a reality in Chile, because every year more immigrants arrive seeking to improve their quality of life, mostly from Latin American countries. This phenomenon is observed in Chilean classrooms, where immigrant students have been incorporated. The objective of this study is to analyze the relationships between teachers’ attitudes toward multiculturalism and their pedagogical practices in schools in the Coquimbo Region, Chile. The research has a quantitative focus, and 88 Chilean professors from different educational levels participated. Information on the variables was collected through the instruments: Attitudes towards Immigration Scale (EAI), Attitudes towards Multiculturalism in School (EAM) Scale and Guide for the Evaluation of Inclusive Practices in the Classroom (GEPIA). Significant correlations were found between the variables. These findings have important educational implications, considering the current Latin American context of constant immigration, evidenced in an ascending way in schools.